Decellularized liver scaffolds effectively support the proliferation and differentiation of mouse fetal hepatic progenitors. Issue 4 (4th June 2013) - Wang, Xiaojun; Cui, Jing; Zhang, Bing‐Qiang; Zhang, Hongyu; Bi, Yang; Kang, Quan; Wang, Ning; Bie, Ping; Yang, Zhanyu; Wang, Huaizhi; Liu, Xiangde; Haydon, Rex C.; et al.
Abstract Decellularized whole organs represent ideal scaffolds for engineering new organs and/or cell transplantation. Here, we investigate whether decellularized liver scaffolds provide cell‐friendly biocompatible three‐dimensional (3‐D) environment to support the proliferation and differentiation of hepatic progenitor cells. Mouse liver tissues are efficiently decellularized through portal vein perfusion. Using the reversibly immortalized mouse fetal hepatic progenitor cells (iHPCs), we are able to effectively recellularize the decellularized liver scaffolds. The perfused iHPCs survive and proliferate in the 3‐D scaffolds in vitro for 2 weeks. When the recellularized scaffolds are implanted into the kidney capsule of athymic nude mice, cell survival and proliferation of the implanted scaffolds are readily detected by whole body imaging for 10 days. Furthermore, epidermal growth factor (EGF) is shown to significantly promote the proliferation and differentiation of the implanted iHPCs. Histologic and immunochemical analyzes indicate that iHPCs are able to proliferate and differentiate to mature hepatocytes upon EGF stimulation in the scaffolds. The recellularization of the biomaterial scaffolds is accompanied with vascularization. Taken together, these results indicate that decullarized liver scaffolds effectively support the proliferation and differentiation of iHPCs, suggesting that decellularized liver matrix may be used as ideal biocompatible scaffolds for hepatocyte transplantation. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1017–1025, 2014.